2002
DOI: 10.1088/0034-4885/66/1/201
|View full text |Cite
|
Sign up to set email alerts
|

Stretching of macromolecules and proteins

Abstract: In this paper we review the biophysics revealed by stretching single biopolymers. During the last decade various techniques have emerged allowing micromanipulation of single molecules and simultaneous measurements of their elasticity. Using such techniques, it has been possible to investigate some of the interactions playing a role in biology. We shall first review the simplest case of a non-interacting polymer and then present the structural transitions in DNA, RNA and proteins that have been studied by singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
280
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(295 citation statements)
references
References 105 publications
13
280
1
1
Order By: Relevance
“…2 A provide key information that is directly extracted from standard MT measurements for positive n t , namely, the values of the buckling transition, n b , and the slope, dL e =dn t (56). In considering the behavior of bare DNA in this study, according to a standard model for bare DNA (56), n b and dL e =dn t are predicted to display power-law dependence as a function of the imposed force, F. In the standard model, doublestranded DNA can be simply represented as an elastic rod with a torsional constant, C, and a bending constant, B ¼ k B TL P .…”
Section: Discussionmentioning
confidence: 99%
“…2 A provide key information that is directly extracted from standard MT measurements for positive n t , namely, the values of the buckling transition, n b , and the slope, dL e =dn t (56). In considering the behavior of bare DNA in this study, according to a standard model for bare DNA (56), n b and dL e =dn t are predicted to display power-law dependence as a function of the imposed force, F. In the standard model, doublestranded DNA can be simply represented as an elastic rod with a torsional constant, C, and a bending constant, B ¼ k B TL P .…”
Section: Discussionmentioning
confidence: 99%
“…We find that large temporal fluctuations of extension arise at one of the boundaries of the denaturation region. Finally, we interpret the experimental data with a simple mechanical model obtained by considering a denaturation term to the classical energy [17] used to describe the buckling transition.Several MT apparatuses have already been reported in the literature and, in our set up [12], we generally follow the most classically proposed schemes [8,19]. The technique is based on the following procedure: one end of the DNA is connected by standard biochemical techniques [8] to a commercial micron-sized superparamagnetic bead and the other DNA end is fixed to the inner wall of a squared capillary tube [20,21].…”
mentioning
confidence: 99%
“…The initial pioneering MT studies focused on the topology of DNA molecules and showed that torsion can produce a so-called "plectoneme", which reduces DNA extension [15,16]. For modeling plectoneme formation, the DNA can be simply described as an elastic rod [17]. The experiments showed that the plectonemes disappear when the force becomes sufficiently high and the direction of the torsion is toward the unwinding of the DNA double helix [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations